Landsgemeinde – demokracja na świeżym powietrzu. Czy głosowanie jawne nadal ma sens? - Kużelewska, Elżbieta (Political Preferences, 2017)
Landsgemeinde – open-air democracy. Does evident voting still matter? The aim of this paper is to discuss specific form of decision-making process – Landsgemeinde. Landsgemeinde (i.e. open assembly) is one of the oldest and the simplest forms of direct democracy practiced in two German-speaking cantons: Glarus and Appenzell Innerrhoden. This assembly democracy survived in Switzerland for more than 600 hundred years and became part of Swiss identity. The article explores both advantages as well as defects of this institution. Key words: Landsgemeinde, Switzerland, open assembly, direct democracy, open-air democracy